Sectorial Macroeconomic Interdependencies : Evidence for Latin America, East Asia and Europe - Loayza, Norman (IMF Working Papers; Working Paper ;, 1999)
This paper analyzes common economic patterns across countries and economic sectors in Latin America, East Asia and Europe for the period 1970-94 by means of an error-components model that decomposes real value added growth in each country into common international effects, sector-specific effects and country-specific effects. We find significant comovements in the European and East Asian samples. In the Latin American sample, however, we find country-specific components to be more important than common patterns. These results are robust to different sub-sample time spans and different sub-sample country groups.